Establishing national normative values for adolescent body composition in Brazil using bioelectrical impedance analysis (BIA): a cross-sectional study of 59,000 adolescents - Teixeira, Fernando Guimarães; Motta, Flávio Andrade Amaral; Sá Filho, Alberto Souza de; Oliveira Silva, Iransé de; Leonardo, Patrícia Sardinha; Lopes-Martins, Rodrigo Alvaro Brandão (Frontiers in Nutrition, 2025)
BackgroundReliable normative references for adolescent body composition are essential for screening and surveillance, yet Brazilian data at national scale remain scarce and heterogeneous across methods and devices.ObjectivesTo generate age- and sex-specific reference curves for phase angle (PhA), skeletal muscle mass index (SMMI), and muscle-to-fat ratio (MFR) in Brazilian adolescents, and to present device- dependent body fat percentage (%BF) percentiles as secondary, interpretation- cautioned outputs.MethodsWe analyzed a frozen, de-identified extract of routine multi- frequency bioimpedance assessments (10.00–19.99 years) spanning all five Brazilian macro-regions and multiple recruitment contexts (schools, clinics/primary care, private practices, gyms/fitness centers, community programs). The extract is produced by a vendor privacy/QA pipeline compliant with LGPD; upstream cleaning logs are not accessible to the authors. Prespecified plausibility and deduplication rules (anthropometry and impedance thresholds; robust BIVA on R/H and Xc/H) were re- applied and yielded no additional exclusions. Sex-specific age curves were modeled with GAMLSS (LMS) to estimate smoothed percentiles (P3, P10, P25, P50, P75, P90, P97). %BF, derived from a proprietary embedded equation, is reported as secondary.ResultsThe analytic cohort comprised 59,000 adolescents from all macro-regions and diverse contexts. Median PhA, SMMI, and MFR increased with age in boys and showed the expected attenuated or plateauing patterns in girls across mid- to late adolescence. Percentile spreads widened with age for muscle-related indices, indicating growing interindividual variability. Device-dependent %BF percentiles exhibited age- and sex- specific trajectories consistent with physiological expectations but should be interpreted with caution pending external validation.ConclusionsWe provide national reference percentiles for PhA, SMMI, and MFR that are immediately useful for clinical and public- health applications and less sensitive to device-specific assumptions. %BF curves are offered as secondary and require independent validation against a criterion method before routine use. Future work should confirm regional representativeness and cross-device portability.